Sistem Pewarisan Horizontal Seni Tradisional Parrawana Di Puppalawo Polewali Mandar - Azwan Dermawan; Jamilah; Nurwahidah (VisArt: Jurnal Seni Rupa dan Design, 2025)
This study is a analysis study to identify and describe the Horizontal Inheritance System of Parrawana Traditional Art in Puppalawo Polewali Mandar. This study aims to answer the problem regarding the Horizontal Inheritance System of Parrawana Traditional Art in Puppalawo Polewali. As a cultural heritage, this traditional art needs to be preserved so that it continues to exist in society today. The urgency of the problem is how the inheritance system of Parrawana traditional art is in educational institutions in Puppalawo Polewali Mandar and how the inheritance system of Parrawana traditional art is in art studios in Puppalawo Polewali Mandar. The method used is descriptive qualitative, namely by describing the research object directly. Data collection techniques are literature studies, observations, interviews, and documentation. Through this study, it is hoped that the wider community will know how the inheritance system of Parrawana art is in Puppalawo Polewali Mandar for its supporting community, thus this art can continue to exist and become one of the commitments to preserving cultural heritage, one of which is Parrawana art in Puppalawo Polewali Mandar.